Synthesis and characterization of 3-cyclohexyloxy-2-hydroxypropyl acrylate and its homopolymer - Coskun, M; Erten, H; Ahmadov, MA; Ozdemir, E (Marcel Dekker Inc, 1996)
3-Cyclohexyloxy-2-hydroxypropyl acrylate was prepared from acrylic acid, cyclohexanol and epichlorhydrin. Polymerization of the monomer was carried out in 1,4-dioxane solution in presence of benzoyl peroxide as initiator. The monomer and the polymer microstructure were investigated by H-1 and C-13 nuclear magnetic resonance (NMR) and infrared techniques. Some properties of the homopolymer were also determined.
Keywords: 2-Hydroxyethyl Methacrylate; Copolymers; Acid